Analisis Peramalan (Forecasting) Penjualan Jasa Pada Warnet Bulian City di Muara Bulian - Fauziah Fauziah; Yulia Istia Ningsih; Eva Setiarini (Universitas Batanghari Jambi, 2019)
In the business world Forecasting is one of the most important factors that must be applied in a business. Forecasting is a method for estimating a value in the future by using past data effectively and efficiently. This research was conducted at Warnet Bulian City In this study, the author discusses the analysis of forecasting (Forecasting) sales of services at the Bulian City internet cafe in Muara Bulian. Forecasting is done using three methods namely the MOVA (Moving Average) method, the WMA (Weight Moving Average) method and the Exponential Smoothing Method by comparing the smallest error rate Forecasting using the MA (Moving Average) method for 3 periods is predicted the level of profit to be gained by Bulian City Warnet in August amounted to. 11,117,833 with MAD 1,487,370. Forecasting using the Weigh Moving Averages (WMA) 3 method is forecasted at 12,287,300 with MAD Error 3,016,016 while the forecast using the double exponential smoothing method is 13,522,572 with MAD 5513617,364 then the forecasting method chosen is the Single Exponential Smoothing method with the Forecast value in August 2018 9,581.69 for the The Forecast Error is MAD of 1,378,375 which is the method with the smallest error rate.